An online immunohematology educational resource for post-graduate hematology trainees: LearnSerology.ca. (February 2023) - Arsenault, Valérie; Yan, Matthew T.S.; Tait, Gordon; Lewin, Antoine; Pendergrast, Jacob
Abstract: Background: Canadian hematology residents are required to demonstrate competencies in transfusion medicine by the end of their 2-year training. Prior evaluation of final year trainees revealed significant variation in knowledge. To address the lack of standardization in serology teaching, an online educational immunohematology resource was created and evaluated. Study design and methods: All Canadian post-graduate trainees completing a residency program in adult hematology during the 2018/2019 academic year were invited to participate. Only trainees from one university were exposed to the program curriculum. A validated exam was administered to trainees at both exposed and unexposed sites at the start of the academic year as a pre-test and in the following year as a post-test. The effectiveness of the program was assessed by both comparing the degree of improvement from pre- to post-test, and by comparing performance on the post-test. Results: 57 trainees from 13 universities completed the pre-test, and 45 trainees from 14 universities completed the post-test. A strong trend towards better performance in the exposed vs non-exposed trainees on the post-test was observed, and the difference was more pronounced, and statistically significant, when analysis was limited to two questions relating to interpretation of an antibody investigation panel. Discussion: LearnSerology.ca is effective and may be potentially superior to traditional immunohematology teaching. The interactive capability of the platform can improve skills related to the resolution of red cell antibody panels.